Integrating Ki Hadjar Dewantara’s Among System into Science Learning Management - Nenah Eja Widiawati; Taufani Chusnul Kurniatun (Jurnal Penelitian Pendidikan IPA, 2026)
Science learning in Indonesian schools continues to face structural and instructional challenges, particularly in laboratory management, inquiry-based implementation, science literacy development, and supervision of science instruction. Effective principal leadership plays a crucial role in ensuring that science learning is systematically planned, implemented, and evaluated. This study examines how Ki Hadjar Dewantara’s Among System can be integrated into science learning management to strengthen principals’ instructional leadership. Using a qualitative literature review approach, this study analyzes empirical research on science education leadership and Dewantara’s educational philosophy. The findings indicate that Dewantara’s leadership trilogy ing ngarsa sung tuladha, ing madya mangun karsa, and tut wuri handayani, supports science learning management through strategic laboratory planning, participative supervision of science teachers, collaborative curriculum development, and the promotion of inquiry-based learning. The Among System encourages structured autonomy in scientific exploration while maintaining professional accountability. However, institutional rigidity, limited laboratory facilities, and administrative constraints remain significant challenges. Integrating Dewantara’s philosophy into science learning management provides a culturally grounded and humanistic leadership framework that enhances instructional quality, scientific literacy, and sustainable school improvement.